DOES IFRS S1/S2 ENHANCE ESG DISCLOSURE QUALITYAND INVESTOR CONFIDENCE? A CONCEPTUAL SYNTHESIS - Okoye, Peter; Fahmi, Fadzlina Mohd; Ali, Mazurina Mohd (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
Weak comparability, limited credibility, and low decision-usefulness of ESG disclosures continue to undermine investor confidence despite rapid global growth in sustainability reporting. As IFRS S1 and IFRS S2 become the emerging global baseline for sustainability standards, there remains limited conceptual understanding of how these standards can enhance ESG reporting quality and market trust. This study conducts a systematic conceptual synthesis of 44 peer-reviewed articles (2021–July 2025) using SPAR-4-SLR and PRISMA frameworks to explain the mechanisms through which IFRS S1/S2 adoption improves ESG quality. The review shows that comparability, readability, and assurance serve as key channels to strengthen completeness, interpretive clarity, and credibility of sustainability reports, thereby increasing investor confidence. A mechanism-based model and four propositions are developed, highlighting contextual influences such as regulatory enforcement and industry sensitivity, and offering a structured agenda for future empirical research.